IbM KELOMPOK USAHA DODOL MANGGA DI DESA SATREYAN KECAMATAN MARON KABUPATEN PROBOLINGGO - Mustofa Mustofa (RELASI : JURNAL EKONOMI, 2017)
Dodol Mangga Business Group has a strategic role and function in improving family economy in facing the fall of local mango price due to mango import rush. With the creativity of mothers housewives made dodol mango to increase the economic value of local mango fruit because at harvest time of local mango fruits fall once the price in the market. This makes the manga farmers excited again in maintaining and managing well manga plants after recent years poorlymaintained. IbM's specific aims are; (1) Dodol Mangga Business Group obtains formal legal management from the Department of Industry and Trade and Cooperatives and SMEs. (2) The realization of micro business group that can become the economic fund of poor family in village area, and become alternative design of poverty alleviation in other area in Indonesia (3) The realization of micro business empowerment concept which is generally managed by poor household, become an inspiration for micro business groups in other regions. (4) Such a model will be the Journal. The method to achieve the target is done by training and mentoring activities for the board and all members of Dodol Mangga Business Group. Training and mentoring focused on group management, product quality and quantity improvement, methods of penetrating market access, simple accounting basics, and legal processing of Dodol Mangga Business Group.